The Influence of Carbon Tax On Financial Sustainability Of South Africa’s Cement And Mining Industry. - Thomas NYAHUNA; Mishelle DOORASAMY (Indonesia Strategic Sustainability, 2022)
This paper examines the impact of carbon tax on financial sustainability of cement and mining companies in South Africa listed on the Johannesburg Stock Exchange. Quantitative research method was used. Correlation analysis was used to analyse the data. Secondary data in form of annual integrated reports, sustainability reports and annual audited financial statements from 2016 to 2020 were used as sources of the variables. The results show that carbon tax adversely influences net profit margin. Therefore, this suggests that carbon tax also negatively impacts shareholders’ dividends. Therefore, this suggests that carbon tax also negatively impacts shareholders’ dividends. This study is significant to policy makers by providing valuable information relating to the effect of carbon pricing decisions on the profitability of the cement and mining sector in South Africa. This gives the policy makers an evidence-based opportunity on designing and developing policies that take into consideration that carbon tax is reducing financial performance of the corporate sector in South Africa. This study contributes to the contemporary literature on nexus between carbon tax and financial sustainability from developing country perspective. Furthermore, this is the first empirical study in South Africa focusing on this relationship.